Studi Prevalensi Teknologi Terhadap Resitensi Pembangunan Manusia di Era Society 5.0 - Indrasto, Haryo Bimo Budi; Nugroho, Jodi Setyo; Salsabila, Fina; Andriyani, Nur (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
This research investigates the influence of the factors contributing to the Human Development Index (HDI) and the degree of technological openness on human development within the regions of Java and Borneo during the period from 2018 to 2023. Employing panel data alongside the Generalized Method of Moments (GMM) estimation approach, the findings indicate that technological openness, gross domestic product per capita, educational density per capita, net enrollment ratios, and life expectancy exert a significant effect on HDI. In Java, the economic and educational variables demonstrate a more pronounced impact, facilitated by superior infrastructure. Conversely, in Borneo, the participation in education and the level of technological openness asume an critical role, exhibiting a more substantial influence in the short term. These results underscore the imperative for region-specific policy interventions, which should encompass the augmentation of technological accessibility, the promotion of equitable economic advancement, and the fortification of educational and healthcare infrastructure. Through the implementation of appropriate strategies, disparities in human development can be mitigated, thereby fostering the attainment of sustainable development goals (SDGs).